Analysis of Error in Working of Questions on the Semester Final Exam of Mathematics Statistics for Students of UIN Saizu Purwokerto - Mutijah Mutijah (PARADIKMA: JURNAL PENDIDIKAN MATEMATIKA, 2023)
Learning evaluation of the certain subject is important to be done in university. It is to be able to see, improve and increase the quality of learning outcomes. One  form of evaluation for a Mathematics Statistics course is the final semester exam, abbreviated as UAS. Purpose of this article to determine the error type of students  in working the final semester exam, percentage of students who do mistakes and amount of error on each type, as well the most mistakes . Research used a  quantitative descriptive method imposed on all of population as many as 98 respondents. Data collection used documentation and the data analysis that is statistics descriptive. Research results showed that as many as 14 type of error with one among them is findings a new of error type. Percentage of students do error on each type is the concept error 96.94%, principle 92.86%, fact 20.41%, conclusion no used correct reasoning 8.16% , error because procedure or algoritm  4.08%, skill error 21.43%, error without pattern 37.76%, technical 3.06%, and error in mark 5.1%, and successive types of error that is data error , operation , write the exact same long answer to two different questions, language interpretation, as well finishing error each of which is 1.02%. The same as in according of the type errors are found percentage of the number of errors that is 40.12%,  28, 09%, 6.17%, 2.47% , 1.23%, 6.48%, 11.42%, 0.93%, 1.54%, and the others is 0.31% respectively. Most mistakes  is the concept error.